Certified organic cropland in the United States: Is perceived value reality? - Stickel, Erin (My University, 2020)
Valuation of farmland in the United States is reliant on farm income, which relates to geographical factors, social and environmental pressures and commodity demands. In recent years, interest in certified organic cropland has emerged throughout the United States at an exponential level. Perception continues to evolve where cropland that undergoes certification and organic production could lead to increased land value and warrant higher returns for landowners in a cash rent scenario across the United States. In this study, a survey of over 400 certified organic landowners and farmers was conducted, and 109 viable responses utilized for analysis of land valuations in the central Midwest, Southern Plains, and East Coast. Data was evaluated from the respondents on a variety of topics such as length of the farmland lease/rent agreement, gross value of the organic commodities raised, and price of non-organic cash rents being paid, with the main objective of securing data about cash rent and land values and for certified organic farmland. Additional analysis of United States Department of Agriculture (USDA) National Agricultural Research Statistics Survey (NASS) for cash rents, environmental data, and regional net farm income in relation to certified organic cropland is discussed, but not directly included in this standard linear regression model. Case studies and literature reviews on this subject in the United States have been conducted and more data is being analyzed each year. Data from this study indicates that while the perception from landowners is that certified organic farmland should be worth more from a cash rent standpoint, the reality is that there still many are unknown pressures on land valuations and few credible statistical relationships were discovered in comparison to prices paid for cash rent of certified organi cropland in the central Midwest, Southern Plains, and East Coast. More research is neede to appropriately analyze the impact of organic cropland on cash rent values in these regions.
Keywords: Organic; Cropland; Value; Agricultural Economics; Agribusiness; Linear Regression